Current insights into the mechanism of mammalian immunoglobulin class switch recombination. (4th July 2019) - Yu, Kefei; Lieber, Michael R.
Abstract: Immunoglobulin (Ig) class switch recombination (CSR) is the gene rearrangement process by which B lymphocytes change the Ig heavy chain constant region to permit a switch of Ig isotype from IgM to IgG, IgA, or IgE. At the DNA level, CSR occurs via generation and joining of DNA double strand breaks (DSBs) at intronic switch regions located just upstream of each of the heavy chain constant regions. Activation-induced deaminase (AID), a B cell specific enzyme, catalyzes cytosine deaminations (converting cytosines to uracils) as the initial DNA lesions that eventually lead to DSBs and CSR. Progress on AID structure integrates very well with knowledge about Ig class switch region nucleic acid structures that are supported by functional studies. It is an ideal time to review what is known about the mechanism of Ig CSR and its relation to somatic hypermutation. There have been many comprehensive reviews on various aspects of the CSR reaction and regulation of AID expression and activity. This review is focused on the relation between AID and switch region nucleic acid structures, with a particular emphasis on R-loops.